Spatiotemporal variation of reference evapotranspiration during 1954–2013 in Southwest China. (16th June 2017) - Feng, Yu; Cui, Ningbo; Zhao, Lu; Gong, Daozhi; Zhang, Kuandi
Abstract: Analysis of temporal trend and spatial variation of reference evapotranspiration (ET0 ) is important in Southwest China, where water resources are vulnerable under the impacts of climate changes and human activities. The main objective of this study was to analyze temporal and spatial variation of ET0 computed by FAO-56 Penman-Monteith model for 119 stations in Southwest China during the period of 1954–2013. Mann-Kendall test, linear trend, Morlet wavelet analysis and inverse distance weighting interpolation methods were applied for the analysis. The results showed that during the past 60 years, annual sunshine hours, relative humidity, wind speed and precipitation decreased while temperature increased. ET0 decreased at a rate of −1.5 mm per decade, or −0.4,  −0.7,  −0.3, and −0.1 mm per decade in spring, summer, autumn, and winter, respectively. There existed significant periods of 26, 12 and 5a in annual ET0 series based on the Morlet wavelet analysis. Lower and higher ET0 values were found in the northeast and southwest regions both for annual and spring series. These findings will be useful for sustainable planning of water resources under the impacts of climate changes and human activities.